Ultrasonic Blood Flow Measurement in Haemodialysis. Issue 5692 (7th February 1970) - Sampson, D.; Papadimitriou, M.; Kulatilake, A. E.
Abstract : A 5-megacycle Doppler flow meter, calibrated in-vitro, was found to give a linear response to blood flow in the ranges commonly encountered in haemodialysis. With this, blood flow through artificial kidneys could be measured simply and with a clinically acceptable error. The method is safe, as blood lines do not have to be punctured or disconnected and hence there is no risk of introducing infection. Besides its value as a research tool the flow meter is useful in evaluating new artificial kidneys. Suitably modified it could form the basis of an arterial flow alarm system.